Usage of Educational Pedagogical Technologies in Future Pedagogues’ Preparation - Blazheyeva, Zoya; Grygor’yeva, Alla (Pedagogical Discourse, 2012)
Peculiarities of usage of educational pedagogical technologies in future pedagogues’ preparation are studied in the article. Different approaches to the treatise of the notions “technology”, “pedagogical technology” and “technology of education” are analyzed. Tasks and functions of educational pedagogical technologies in educational process are revealed